Bronchial responsiveness and acute bronchodilator response in chronic obstructive pulmonary disease and diffuse panbronchiolitis. Issue 6 (June 1994) - Koyama, H; Nishimura, K; Mio, T; Ikeda, A; Sugiura, N; Izumi, T
Abstract : BACKGROUND–Diffuse panbronchiolitis (DPB) is characterised clinically by chronic airflow limitation and respiratory tract infection, and pathologically by chronic bronchiolar inflammation. To elucidate the functional differences between chronic obstructive pulmonary disease (COPD) and DPB the bronchial responsiveness to methacholine was compared in 64 patients with COPD and 32 patients with DPB, and the bronchodilator response was compared in 72 patients with COPD and 49 with DPB. METHODS–Bronchial responsiveness to methacholine was determined by the dosimeter method and expressed as PD20FEV1, and bronchodilator response was measured as the change in percentage predicted response with 5 mg nebulised salbutamol. RESULTS–Baseline FEV1 was similar in the two groups of patients. Patients with COPD were more responsive to methacholine than were those with DPB (geometric mean PD20FEV1 8.87 v 48.0 cumulative units). Reversibility of air flow obstruction, expressed as the difference between the percentage predicted postbronchodilator FEV1 and prebronchodilator FEV1, was significantly larger in patients with COPD than in those with DPB (7.87 (6.52)% v 4.16 (4.43)%). CONCLUSIONS–The observation that patients with DPB differ substantially in bronchial responsiveness from those with COPD is thought to reflect the difference in the mechanisms of these two diseases–that is, airway disease in DPB and more parenchymal disease in the group of patients with COPD. The nature of bronchiolar inflammation in COPD and DPB is also different, possibly explaining the difference in bronchial responsiveness. More fixed airflow limitation as a result of structural bronchiolar lesions in DPB will explain the smaller reversibility of airflow obstruction.